2015
DOI: 10.1590/1982-021620158014
|View full text |Cite
|
Sign up to set email alerts
|

Nascidos vivos com fissura de lábio e/ou palato: as contribuições da fonoaudiologia para o Sinasc

Abstract: OBJETIVO:caracterizar os casos de fissura de lábio e/ou palato atendidos num centro de referência do estado de Pernambuco e os nascidos vivos notificados ao Sistema de Informação sobre Nascidos Vivos com essa malformação, mensurando a subnotificação dos casos de fissura nesse sistema.MÉTODOS:desenvolveu-se um estudo epidemiológico, cuja população foram crianças nascidas em 2009 e atendidas no centro de referencia para deformidades craniofaciais em Pernambuco, e pelos nascidos vivos no mesmo ano, notificados ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…In this study, the proportion of heredity observed was lower than that reported in the literature, perhaps owing to the reduced sample size. Prevalence of the male gender with unilateral trans-foramen incisor cleft is also described in published epidemiological studies, considering its greater incidence compared with the female gender (12,13) , with the same also occurring with respect to earlier fusing time of the nasal and palatal processes (13) . Regarding cleft lip and/or palate (CLP) surgical correction, despite the different chronology described in the literature (14)(15)(16) , most Speech-language Pathology services recommend that the surgery be performed during the postnatal period, with ideal time for cheiloplasty at three or between three and six months of age, depending on the clinical conditions necessary to perform a risk procedure (2,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the proportion of heredity observed was lower than that reported in the literature, perhaps owing to the reduced sample size. Prevalence of the male gender with unilateral trans-foramen incisor cleft is also described in published epidemiological studies, considering its greater incidence compared with the female gender (12,13) , with the same also occurring with respect to earlier fusing time of the nasal and palatal processes (13) . Regarding cleft lip and/or palate (CLP) surgical correction, despite the different chronology described in the literature (14)(15)(16) , most Speech-language Pathology services recommend that the surgery be performed during the postnatal period, with ideal time for cheiloplasty at three or between three and six months of age, depending on the clinical conditions necessary to perform a risk procedure (2,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Heredity is among the relevant risk factors for occurrence of craniofacial malformations (12) . In this study, the proportion of heredity observed was lower than that reported in the literature, perhaps owing to the reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Information System on Live Births is a reliable source of information for the analysis of live births with orofacial clefts (18,23). Therefore, considering the prevalence found and the negative impact that this condition implies on the quality of life of these children and family members (2,29,30), the care provided by the government to those born with orofacial clefts should be made in a comprehensive way through the adoption of public health policies directed to this population group.…”
Section: Discussionmentioning
confidence: 99%
“…(5). The prevalence of syndromic OFC varies worldwide, ranging, according to the literature, between 1.5% and 63% (6). Among the reported congenital abnormalities were described skeletal system disorders, central nervous system disorders, congenital heart defect (CHD), respiratory system abnormalities, polydactyly, eyes and ear anomalies, limb anomalies, chromosomal disorders, talipes equinovarus, CLP, anencephaly, spina bifida, and many more (7).…”
Section: Conclusõesmentioning
confidence: 99%